Smart angular displacement sensor for agricultural field robot manipulators - Baratov Rustam; Mustafoqulov Almardon (E3S Web of Conferences, 2023)
This study presents the electromagnetic angular displacement sensor and its technical characteristics. The existing electromagnetic angular displacement sensors have been thoroughly analyzed and compared with other types of sensors. The reason for the low sensitivity of the electromagnetic angular displacement sensor has been investigated and some technical modification to the existing sensor has been made. The magnetic circuits of the electromagnetic sensors have been analyzed. A method is proposed for expanding the range of angular measurements up to 180 degrees and increasing the sensitivity of the electromagnetic sensor without compromising the measurement accuracy. This, in turn, allows high-precision control and measurement of rotating mechanisms of all types of mechatronic systems and agricultural robots.